Edaphic macrofauna and soil physicochemical properties, in smallholder coffee farms - Morales Rojas, Eli; Chávez Quintana, Segundo; Chichipe Vela, Elder; Oliva, Manuel; Quiñones Huatangari , Lenin (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Edaphic macrofauna is a biological soil indicator that is rarely applied in the identification of soil quality in coffee farms. The objective was to evaluate edaphic macrofauna and soil physico-chemical properties in four coffee farms at different altitudes. The farms were selected in four hamlets of small-scale coffee farmers. In one-hectare plantations, three monoliths of 25 × 25 cm wide by 30 cm depth were sampled. Soil samples were taken from each plot, then the organic matter (OM) content, hydrogen potential (pH), electrical conductivity (EC) and nitrogen (N) content were determined. There were no differences in macrofaunal diversity for the altitudes studied, but there were differences according to the time of year (rainfall and low water). The maximum Shannon index was 2.2 (rainy season) and 1.1 (dry season). Physico-chemical parameters such as soil pH ranged from 7.8 - 8.15 in the lower altitude farms and for the higher altitude farms it was 6.38 - 6.65. Soil pH was highly negatively correlated with altitude. Nitrogen was positively correlated with organic matter. Faunal diversity is negatively correlated with season and the presence of microorganisms is influenced by the physico-chemical characteristics of the soil.